Dokumenty (wybór Margaux Verdet) / Documents (selected by Margaux Verdet) - Margaux VERDET (Sztuka i Dokumentacja)
From January 27, 1946 to January 5, 1947, Ad Reinhardt published in the magazine PM a series of "art pages"- a term designating full pages presenting drawings and collages. Based on a selection of such pages, the article analyses how the attention paid to the figure of the viewer grants them a fundamental role in the process of defining modern American art. First of all, through considering the viewer's representations, in order to understand the way Reinhardt petitioned the modern observer for active perception and an ethical stance concerning abstract art. Secondly, through analysing representations of the organ of the eye,with regard to the philosophy of Maurice Merleau-Ponty, thus placing sight at the center of the ontological reflection of painting. While a picture asks the viewer “what do you represent?” in a drawing, painting invites the viewer to become aware of their seeing body, and modern painting finds its definition there, its capacity to allow us to see how we see.